Is there still room for additional common susceptibility alleles for venous thromboembolism?. (6th August 2016) - Trégouët, D. A.; Delluc, A.; Roche, A.; Derbois, C.; Olaso, R.; Germain, M.; de Andrade, M.; Tang, W.; Chasman, D. I.; van Hylckama Vlieg, A.; Reitsma, P. H.; Kabrhel, C.; et al.
Abstract : Essentials Genetic architecture of venous thromboembolism (VTE) remains to be fully disentangled. 11 newly discovered candidate polymorphisms were genotyped in 3019 VTE cases and 2605 controls. None of the 11 polymorphisms were significantly associated with VTE risk. Additional major efforts are needed to identify VTE‐associated genetic variants. Summary: Background: Through a meta‐analysis of 12 genome‐wide association studies, the International Network against VENous Thrombosis (INVENT) consortium identified two novel susceptibility loci for venous thromboembolism (VTE). This project has also generated other candidates that need to be confirmed. Objectives: To assess the association with VTE of common single‐nucleotide polymorphisms (SNPs) that demonstrated strong statistical, but not genome‐wide, significance in the INVENT cohorts. Patients/methods: Eleven SNPs were genotyped and tested for association with VTE in three case–control studies totaling 3019 patients and 2605 healthy individuals. Results and conclusions: None of the tested SNPs showed evidence for association with VTE. Different strategies are needed to decipher the whole spectrum of common and rare genetic variations associated with VTE risk.